2014
DOI: 10.1039/c4cy00764f
|View full text |Cite
|
Sign up to set email alerts
|

Palladium catalyzed aryl C–H amination with O2via in situ formation of peroxide-based oxidant(s) from dioxane

Abstract: (DAF)Pd(OAc)2 (DAF = 4,5-diazafluorenone) catalyzes aerobic intramolecular aryl C–H amination with N-benzenesulfonyl-2-aminobiphenyl in dioxane to afford the corresponding carbazole product. Mechanistic studies show that the reaction involves in situ generation of peroxide species from 1,4-dioxane and O2, and the reaction further benefits from the presence of glycolic acid, an oxidative decomposition product of dioxane. An induction period observed for the formation of the carbazole product correlates with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 72 publications
1
42
0
Order By: Relevance
“…More recently, Weinstein and Stahl reported that peroxide species generated in situ from 1,4-dioxane and O 2 acted as the oxidant in palladium catalysed aryl C-H amination reactions. 34 We also tested 2-butanone as a solvent and found that this also resulted in a good yield (Entry 8 Table 2). We presumed that this further supported the idea of in situ formation of organic peroxides that are then acting as oxidants, as 2-butanone and H 2 O 2 can form 2-butanone peroxide (often referred to as MEKP (methyl ethyl ketone peroxide)).…”
mentioning
confidence: 99%
“…More recently, Weinstein and Stahl reported that peroxide species generated in situ from 1,4-dioxane and O 2 acted as the oxidant in palladium catalysed aryl C-H amination reactions. 34 We also tested 2-butanone as a solvent and found that this also resulted in a good yield (Entry 8 Table 2). We presumed that this further supported the idea of in situ formation of organic peroxides that are then acting as oxidants, as 2-butanone and H 2 O 2 can form 2-butanone peroxide (often referred to as MEKP (methyl ethyl ketone peroxide)).…”
mentioning
confidence: 99%
“…The elementary steps of a Pd 0 /Pd II cycle have been seen in similar form for phosphine complexes in aminations reported by the groups of Buchwald and Hartwig . Aerobic oxidation of Pd II to Pd IV and reductive elimination with formation of a C–heteroatom bond from a Pd IV species have been postulated by Mirica and co‐workers for the oxidation of arenes to phenols and by Stahl and co‐workers for the synthesis of carbazoles by intramolecular C−N formation …”
Section: Methodsmentioning
confidence: 94%
“…14 Notably, the only examples in which O 2 was used as the terminal oxidant is for carbazole synthesis, and a limited substrate scope was demonstrated under the reported conditions. 12,13d …”
mentioning
confidence: 99%